(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the goals and objectives of prosecutorial supervision at the stage of initiating criminal proceedings. Furthermore, the main tasks of the prosecutor are to protect the rights and freedoms of individuals and citizens, to prevent and suppress crimes, and to participate in judicial proceedings concerning administrative offenses and criminal cases.